State formation and the politics of land in north-eastern Uganda. Issue 467 (12th January 2018) - Kandel, Matt
Abstract: While most researchers criticize the effectiveness of states in Africa, state formation is proceeding, albeit gradually. This article analyzes state formation along the historically conflict-affected and fragile Karamoja–Teso sub-national border in north-eastern Uganda. I argue that the central state has consolidated control over the north-east and begun the process of politically incorporating Karamoja into Uganda for the first time in history—evidence of state formation. Yet, this success has unintentionally created space for renewed conflict in two ways: (i) a territorial conflict between and within the Teso and Karamoja local states over the legitimate location of the sub-national border, and (ii) rising competition over the utilization of land along the now secure border. I emphasize that tensions surrounding the border are far from a recent development; they are deeply rooted in political, economic, and cultural processes that stretch back centuries. This article makes the argument for evaluating state formation in Africa over the longue durée . It also seeks to build on recent work which underlines the historically contingent and shifting dynamics that shape, enable, and constrain state making in Africa.